Tourism, Peace and National Development - Muhammad Abdullahi; Sadiq Lawan (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: The purpose of the study is to identify the tourist attractions available in Northern Nigeria, and unveil the relationship between tourism and peace, as well as tourism and national development in the region. It attempts to understand the perception of respondents on whether tourism has any significance in building peace and contributing to national development in Northern Nigeria. Method: The study adopts a mix method of quantitative and qualitative. Data was generated through structured questionnaire and complemented with a desk review of literature. Convenience Sampling was utilised in collecting data from 522 respondents in Kaduna (56), Kano (62), Kebbi (42), Katsina (45), Sokoto (54), Borno (63), Yobe (58), Bauchi (47), Adamawa (41), and Taraba (54) States of Northern Nigeria. Result: The study revealed that northern Nigeria has numerous tourist attractions that have not been appreciated and highly under-utilised. The findings contradict the existing literature that tourism contributes to peace largely because of the poor awareness that respondents have on the tourist attractions in their region as well as their inability to utilise those sites for meaningful purposes. However, other findings of the study are in compliance with existing studies which posits that tourist attractions contributes to national development especially on the economic aspects. The study acknowledges the relevance of tourism to research purposes, as well as an avenue for promoting socio-cultural values. Contribution: The paper contributes to the existing research based literature and debates on tourism and its relationship with peacebuilding and national development. It presents a location specific opinion of respondents on tourist attractions which will be used for empirical reference purposes. It will therefore benefit writers in the field of tourism to understand the current perception of individuals thereby exploring further into specifics of how investments in tourism can enhance peaceful co-existence and national development. Governments will find the piece useful as it will help in formulating policies and establishing institutions capable of reviving the tourism and socio-cultural economy at large.